Factors Influencing E-WOMs in Restaurant Business: Evidence from Bangladesh - Fakir, Md Kawshar Jahan; Miah, Md Rukon (Goodwood Publishing, 2021)
Purpose: The study aimed to inquire about the factors influencing E-WOMs in the restaurant business: Evidence from Bangladesh. Research Methodology: Quantitative research was conducted and the study used descriptive research methodology. 161 data points were gathered from Bangladeshi customers using a standardized questionnaire and an online purposive sampling technique. The partial least square structural method was used to analyze the data and test the hypotheses. Sampling Technique: The probability sampling technique was chosen for this study. An online questionnaire is coherent with the conditions of this study, which focuses on a person who visited a restaurant. Data Analysis: SmartPLS software version 3.0 was used to analyze the data. Structural equation modeling was used to validate the study's conceptual model (SEM). Cronbach’s Alpha coefficients and Composite Reliability (CR) are used to determine the reliability. Besides, discriminant validity is used to test the Fornell-Larcker Criterion. Results: PLS-SEM demonstrated that positive reviews, negative reviews, trust, food and service quality, and source credibility had significant effects on E-WOMs in the restaurant business in Bangladesh. Limitation: This study focused only on the Bangladeshi restaurant business. Contribution: The study helped the authorities conduct their restaurant business by considering these factors, positive reviews, negative reviews, trust, food and service quality, and source credibility.